Data Mining Implementation with Clustering Techniques for Drug Inventory Information in Antonius Hospital Pontianak - Antonius Anton (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2020)
Competition in the business world, especially in the pharmacy industry, requires developers to find a strategy that can increase sales of special drug sales by maximizing service to consumers. One way is to keep the availability of various types of drugs in the pharmacy warehouse. To find out what medicines are purchased by consumers, it can be done using basket analysis techniques, namely analysis of consumer buying habits. Detection of drugs that are often bought together is called the association rule. Medication is an important factor whose availability must be controlled properly in a hospital. The availability of drugs at the hospital will support hospital performance. One of the data mining methods that can be used from the above analysis is the clustering method, which is grouping data items into small groups so that each group has an essential equation. The evaluation results from this study are grouping drug data with clustering techniques to facilitate the process of grouping drugs based on drugs that are often used in a certain period of time